JANUBIY OROLBO‘YI KSILOFAG-HASHAROTLARI DOMINANT TURKUMLARINING (INSECTA:COLEOPTERA, ISOPTERA, LEPIDOPTERA, HYMENOPTERA, DIPTERA) BIOEKOLOGIK XUSUSIYATLARI - Juginisov , T.I.; Alimbetov А.А; Аsemenova D.Y; Ro‘zimatova , F.SH; Ubaydullayeva , E.A. (Actual problems and prospects of the study of the fauna, 2024)
This article says that one of the main reasons for the reproduction of xylophagous insects is the fact that a large part of the natural biotope of the Southern Aral Sea is found in sandy-desert areas, which is an exceptional place for the development of pests.